Safety and Efficacy of HFA-134a Beclomethasone Dipropionate Extra-Fine Aerosol over Six Months - Louis-Philippe Boulet; André Cartier; Pierre Ernst; Pierre Larivée; Michel Laviolette (Canadian Respiratory Journal)
OBJECTIVE: To compare the systemic safety and efficacy of hydrofluoroalkane beclomethasone dipropionate (HFA-BDP) extra-fine aerosol 800 µg/day with chlorofluorocarbon (CFC)-BDP 1500 µg/day.